China's Middle East Foreign Policy: A Soft Power Approach and Human Right Issues - Husain, Andi Subhan; Sahide, Ahmad (Technium Social Sciences Journal, 2023)
By strengthening its relationship with Middle Eastern countries, China continues to increase the security of its Middle Eastern oil imports. The “three ugly forces” of terrorism, national separatism, and religious extremism are something that the Chinese would like to fight against in terms of security. This article examines China’s Middle East foreign policy in the Middle East, soft power business tactics, and human rights issues. Through an analytical and descriptive approach, data were analyzed utilizing the deductive technique of research. To provide a qualitative interpretation of the subject of this article, these data were then processed, validated, and reviewed using the theories of peaceful rise and peaceful development in foreign policy as a theoretical review. The results of this study showed that China promotes a style of Chinese diplomacy in which China will not interfere with domestic political matters or the human rights issues of other countries. China will not put strict requirements on humanitarian assistance or investment. Three fundamental concepts define China’s relations with the Middle Eastern countries: sovereignty projection, the right to protect sovereignty, and non-interference in the internal affairs of other states. The novelty of this research focuses on China’s soft power and human rights in the Middle East rather than on Joseph Nye’s three pillars of soft power: political values, culture, and foreign policy.